Identifikasi Tingkat Kematangan Buah Pisang Menggunakan Metode Ektraksi Ciri Statistik Pada Warna Kulit Buah - nina sularida limin; Jayanti Yusmah Sari; Ika Purwanti Ningrum Purnama (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
Abstract—The Banana (musa paradical) is one of the national superior fruit production which is rich in vitamins. The level of banana production in Indonesia is above other fruit commodities. However, one of the postharvest problems for bananas produced on a large scale or industry is in the sorting of bananas. During this time the banana fruit is identified by the level of maturity based on the analysis of the skin color of the fruit visually the human eye that has limitations. The identification process like this has several disadvantages including requiring more energy to sort, and the level of perception of fruit maturity produced can be different because humans can experience fatigue, not always consistent, and human judgment is also subjective. To overcome this problem, this study builds a system to identify the maturity level of bananas using the extractive method of statistical features based on the skin color of bananas. The statistical feature extraction method used in this study is the maximum, minimum, and mean values ​​of pixels for RGB and HSV color spaces. The system built has been tested using 40 datasets of image of bananas and shows the results of good accuracy. Index Terms—enter key words or phrases in alphabetical order, separated by commas